Losartan in postmenopausal women with essential arterial hypertension - O. N. Tkacheva; A. V. Barabashkina; I. M. Novikova; N. V. Sharashkina (Кардиоваскулярная терапия и профилактика)
Aim. To study losartan effectiveness and safety in postmenopausal women with essential arterial hypertension (EAH), and with or without hormone replacement therapy (HRT). Material and methods. In total, 58 postmenopausal women with EAH were followed up for 6 months after being administered antihypertensive therapy (AHT) with losartan, due to inadequate blood pressure (BP) control. Group I (n=30) did not receive HRT, while Group II (n=28) was administered HRT. Losartan effects on BP dynamics, endothelium-dependent vasodilatation (EDVD), intima-media thickness (IMT) of carotid arteries (CA), lipid and carbohydrate metabolism were assessed, as well as losartan tolerability. Results. Losartan therapy resulted in target BP level achievement in both groups. At the study end, EDVD increase was statistically significant in Group I (р<0,05) and highly significant in Group II (р<0,001). In both groups, a tendency towards CA IMT reduction was observed. In all participants, a positive dynamics of lipid profile was observed, but it reached statistical significance only for low-density lipoprotein cholesterol in Group II. After 6 months, insulin sensitivity was normalized in all patients. The tolerability of losartan was good throughout the study period. Conclusion. In postmenopausal women with AH, adding losartan to the AHT scheme demonstrated good antihypertensive effectiveness, insulin sensitivity normalization, endothelial function and lipid profile improvement. Among women receiving AHT and HRT, antihypertensive effect, as well as beneficial effects on endothelial function and lipid profile, was greater than in women receiving AHT only.